'Guests of the British Crown': White Russian Refugee Camps in Egypt, 1920–1922. (2nd January 2021) - Konn-Roberts, Tania
ABSTRACT: During the closing stages of the Russian Civil War in south Russia Novorossiisk, a port on the Black Sea coast, provided an escape route to the Crimea for the defeated White Russian forces. During the early months of 1920 the port was also crowded with civilians desperate to escape the consequences of the imminent Bolshevik victory. British funded and crewed ships helped thousands to get away. Of these, despite instructions to the contrary from London, some were landed in Egypt. In the great diaspora of White Russians that followed the final victory of Bolshevism all faced challenging circumstances, but the experiences of the refugees in Egypt were untypical in many respects.